A review on the notions of food heritage conservation - Kamaruzaman, Mohd Yusof; Ab. Karim, Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2022)
The topic heritage has been researched more these days for the simple reason that it needs re-searching. It can be tangible to the senses and intangible as abstract ideas which both are equally susceptible to extinction. In the intangible heritage, food is despite its tangible dynamic sensorial attributes, it is also non-material in existence as the true heritage lies in the ideas, recipes, methods, cultures, and practices of making rather than the food itself. These instances mentioned, also could mean for varying comprehensions across the globe. This paper argues on the global differences in the basics of food heritage and its aspects as well as how it is compared to Malaysia’s notions of the topic. Inevitably, this includes the issues of traditional food authenticity, as elusive features of perfection, are deemed to be obligatory. Understanding the basics is vital for Malaysia to strengthen its food heritage antiquity against globalization’s compromises. Henceforth, this review article discusses the perceived authenticity and introducing artisanal food to better understand the heritage food’s production.